2021
DOI: 10.3390/brainsci11091193
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Cord Injury-Induced Changes in Encoding and Decoding of Bipedal Walking by Motor Cortical Ensembles

Abstract: Recent studies have shown that motor recovery following spinal cord injury (SCI) is task-specific. However, most consequential conclusions about locomotor functional recovery from SCI have been derived from quadrupedal locomotion paradigms. In this study, two monkeys were trained to perform a bipedal walking task, mimicking human walking, before and after T8 spinal cord hemisection. Importantly, there is no pharmacological therapy with nerve growth factor for monkeys after SCI; thus, in this study, the changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 74 publications
(91 reference statements)
0
2
0
Order By: Relevance
“…Among them, Frame DIAS (21 studies: e.g., Mori et al, 2006;Higurashi et al, 2010;Goto et al, 2021), Simi Motion (five studies: Fitzsimmons et al, 2009;Capogrosso et al, 2016;Vouga et al, 2017;Tseng et al, 2019;Xing et al, 2019), Peak Motus software (four studies: Courtine et al, 2005a,b;Larson and Demes, 2011;Demes and O'Neill, 2013), and Xcitex (seven studies: e.g., O'Neill et al, 2015;Thompson et al, 2018;Young and Chadwell, 2020) were commonly used (n = 37; 52.1%). The remaining 34 studies used self-written programs based on development platforms, such as MATLAB (Reghem et al, 2013(Reghem et al, , 2014Pontzer et al, 2014;Dunham et al, 2018) and C++ (Peikon et al, 2009), or manually observed and analyzed videos or photos to obtain spatial-temporal parameters (Kimura, 2000;Nakano, 2002;Ma et al, 2016;Hu et al, 2021).…”
Section: Ipsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, Frame DIAS (21 studies: e.g., Mori et al, 2006;Higurashi et al, 2010;Goto et al, 2021), Simi Motion (five studies: Fitzsimmons et al, 2009;Capogrosso et al, 2016;Vouga et al, 2017;Tseng et al, 2019;Xing et al, 2019), Peak Motus software (four studies: Courtine et al, 2005a,b;Larson and Demes, 2011;Demes and O'Neill, 2013), and Xcitex (seven studies: e.g., O'Neill et al, 2015;Thompson et al, 2018;Young and Chadwell, 2020) were commonly used (n = 37; 52.1%). The remaining 34 studies used self-written programs based on development platforms, such as MATLAB (Reghem et al, 2013(Reghem et al, , 2014Pontzer et al, 2014;Dunham et al, 2018) and C++ (Peikon et al, 2009), or manually observed and analyzed videos or photos to obtain spatial-temporal parameters (Kimura, 2000;Nakano, 2002;Ma et al, 2016;Hu et al, 2021).…”
Section: Ipsmentioning
confidence: 99%
“…NHP studies of intracortical neural recordings or BCI were based on home-made (e.g., HermesB) or commercial neural recording systems (e.g., Blackrock Microsystems, Salt Lake City, UT, USA; FHC Inc., Bowdoin, ME, USA). EMG studies employed implantable electrodes (Yin et al, 2014;Hu et al, 2021;Shitara et al, 2022b) or surface EMG sensors (Nakano, 2002;Goetz et al, 2012;Wei et al, 2019). Ma et al (2016) adopted MEP and SSEP to evaluate spinal cord function electrophysiologically in NHP models.…”
Section: Biodevicementioning
confidence: 99%